Novel strategy to treat lung metastases: Hybrid therapy involving surgery and radiofrequency ablation. Issue 14 (9th June 2021) - Hasegawa, Takaaki; Kuroda, Hiroaki; Sakakura, Noriaki; Sato, Yozo; Chatani, Shohei; Murata, Shinichi; Yamaura, Hidekazu; Nakada, Takeo; Oya, Yuko; Inaba, Yoshitaka
Abstract: Background: This study was performed to evaluate the clinical outcomes of hybrid treatment involving surgical resection and percutaneous radiofrequency ablation for patients with multiple lung metastases. Methods: Seventeen patients (6 men, 11 women; median age, 52 years; range, 16–78 years) underwent hybrid treatment involving surgery and radiofrequency ablation to treat multiple lung metastases (median number, 4; range, 2–26) between May 2014 and February 2020. The primary lesions were colorectal carcinoma ( n = 9), uterine endometrial carcinoma ( n = 3), osteosarcoma ( n = 2), renal cell carcinoma ( n = 1), glottic carcinoma ( n = 1), and fibrolamellar hepatocellular carcinoma ( n = 1). Twenty‐four sessions each of surgery and radiofrequency ablation were performed. Safety, disease‐free survival, and overall survival were evaluated. Safety was assessed according to the Clavien‐Dindo Classification. Results: A grade IVa adverse event of empyema developed in one patient (4%, 1/24) after surgery. A grade IIIa adverse event of pneumothorax and a grade II adverse event of lung abscess occurred in four (17%, 4/24) and one session (4%, 1/24) after radiofrequency ablation, respectively. During the median follow up of 34 months (range, 8–67 months), 10 patients (59%, 10/17) developed new metastases. The 5‐year disease‐free survival rate was 32%. Four or fewer lung metastases ( p = 0.008) and metastases from colorectal carcinoma ( p = 0.02) were factors significantly associated with longer disease‐free survival. One patient (6%, 1/17) died of tumor progression 29 months after initial treatment. The 5‐year overall survival rate was 88%. Conclusions: The strategy of hybrid treatment involving surgery and radiofrequency ablation may offer good outcomes for patients with multiple lung metastases. Abstract : Hybrid therapy involving surgical resection and percutaneous radiofrequency ablation for multiple lung metastases was effective, with 5‐year disease‐free and overall survival rates of 32% and 88%, respectively. Patients with four or fewer lung metastases and metastases from colorectal carcinoma appear to be good candidates for hybrid therapy.